On some Curculionidae incertae sedis (Coleoptera) named by Carl Peter Thunberg (1743–1828) - Prena, Jens (Zootaxa, 2025)
Type specimens of three European and ten South African weevil species named by Thunberg were examined, photographed and classified. Four of them, all from South Africa, have valid or potentially valid names. Acallopistus vitellus (Thunberg, 1813) is the valid name for A. guttatus (Boheman, 1835), new synonym and Gymnetron fimbriatum (Thunberg, 1813), new combination is the valid name for G. hirsutum (Rosenschöld, 1838), new synonym. Eleven other names are referred to Bronchus Germar, Hypera Germar, Isorhynchus Schönherr, Otiorhynchus Germar, Phlyctinus Schönherr and Tanymecus Germar and to the tribes Anoplini, Cyphicerini, Oosomini and Tanyrhynchini.